Fillerless Gas Tungsten Arc Welding of Thin Wall Tube Joint between AISI304 and AISI316L Stainless Steel - Kanchana, Rapee; Kimapong, Kittipong (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to investigate apply a gas tungsten arc welding with non-filler metal for producing a dissimilar material tube joint between AISI304 and AISI316 stainless steel using a welding current range Z90-165A). Tube joints were produced various welding current conditions. Their properties, tensile strength and metallurgical characteristics, were then investigated. The results showed that an optimized welding current that produced maximum tensile strength of 486 MPa and elongation of 18% was 135 A. A width and a penetration of the weld metal that were increased because of an increase of the welding current affected to produce a sound joint and showed higher tensile strength. Increasing welding current that affected to increase a weld bead concave and a root convex of the joint resulted to decrease the joint tensile strength because of a decrease in cross section area for supporting a test load of the joint. A fracture of the tensile test specimen that showed maximum tensile strength was located at the weld metal that was nearly an interface between the weld metal and AISI316L base metal. This result was caused by a dendrite structure characteristic in the AISI316L base metal interface side was coarser than that of the AISI304 base metal interface side.